Analysis of leadership, capabilities, and organizational culture on employee performance through motivation - Jumawan, Jumawan; Ali, Hapzi; Sawitri, Ni Nyoman; Rony, Zahara Tussoleha (Goodwood Publishing, 2025)
Purpose: This study examines the influence of leadership, capability, and organizational culture on employee performance through motivation in the Market XXX. Research Methodology: The method used in this study was descriptive quantitative. The study population consisted of 1,284 employees with a sample of 270 respondents. Primary and secondary data were used in this study. SmartPLS was used as an analytical tool in this study. The tests conducted in this study included the Validity Test, Reliability Test, Inner Model Test, Outer Model Test, and Hypothesis Test. Results: The method used in this study was descriptive and quantitative. The study population consisted of 1,284 employees with a sample of 270 respondents. Primary and secondary data were used in this study. SmartPLS was used as an analytical tool in this study. The tests conducted in this study included the Validity Test, Reliability Test, Inner Model Test, Outer Model Test, and Hypothesis Test. Conclusion: Based on the problem formulation, hypothesis, results, and discussion, it can be concluded that in the XXX market: leadership, capability, and organizational culture each have a positive and significant effect on both motivation and employee performance, either directly or indirectly through motivation Limitations: This study was limited to discussing employee motivation and performance. Generalizations from these findings may be limited by their focus on the XXX market. In addition, although this study used questionnaires/surveys created by the researchers to ensure their relevance, the data used may be subject to bias, such as social desirability or limited disclosure of unfavorable opinions. Contribution: This study contributes to the understanding of the factors that influence employee motivation and performance, such as leadership, capabilities, and organizational culture. Novelty: This study adds new insights into other factors that influence employee motivation and performance, particularly in the XXX market. Thus, it can be used as a reference in future literature.